2015
DOI: 10.1002/mbo3.255
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and determinism of soil microbial community distribution across an agricultural landscape

Abstract: Despite the relevance of landscape, regarding the spatial patterning of microbial communities and the relative influence of environmental parameters versus human activities, few investigations have been conducted at this scale. Here, we used a systematic grid to characterize the distribution of soil microbial communities at 278 sites across a monitored agricultural landscape of 13 km². Molecular microbial biomass was estimated by soil DNA recovery and bacterial diversity by 16S rRNA gene pyrosequencing. Geosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
54
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 56 publications
13
54
1
1
Order By: Relevance
“…However, there is general consensus that biodiversity is positively related to function at the ecosystem level, and this has been demonstrated across national and international scales with strong correlations for functions such as N mineralisation and with system properties such as plant productivity, net primary productivity and litter decomposition Wagg et al, 2014). The interaction between biodiversity and ecosystem function is of relevance to agricultural ecosystems, as land management significantly affects taxonomic and functional biodiversity (Constancias et al, 2015;de Menezes et al, 2015;Mendes et al, 2015).…”
Section: Broad Versus Narrow Functional Biodiversitymentioning
confidence: 98%
See 1 more Smart Citation
“…However, there is general consensus that biodiversity is positively related to function at the ecosystem level, and this has been demonstrated across national and international scales with strong correlations for functions such as N mineralisation and with system properties such as plant productivity, net primary productivity and litter decomposition Wagg et al, 2014). The interaction between biodiversity and ecosystem function is of relevance to agricultural ecosystems, as land management significantly affects taxonomic and functional biodiversity (Constancias et al, 2015;de Menezes et al, 2015;Mendes et al, 2015).…”
Section: Broad Versus Narrow Functional Biodiversitymentioning
confidence: 98%
“…However, increasing WFPS can also decrease the rate of decomposition of bioavailable SOM by limiting oxygen (O 2 ) diffusion and therefore aerobic heterotrophic metabolism, for example reduced turnover of SOM in pores < 6 mm in diameter relative to 6e30 mm in diameter Killham et al, 1993). Although soils of increasing clay content are often associated with both increasing amounts of microbial biomass C (MBC) and SOC (Banu et al, 2004;Constancias et al, 2015;Dalal, 1998), this correlation does not necessarily result in greater rates of C mineralisation (Wardle, 1992). This is indicative of the role of clay in hindering SOM bioavailability.…”
Section: Soil Physical Properties Affecting Som Bioavailabilitymentioning
confidence: 99%
“…In addition, visual comparison of the different maps evidenced that the location of the hot and low spots was different for each microbial parameter and suggested that these variations were related to soil characteristics (as represented by soil types above). Altogether, these observations lead to conclude that various environmental factors drive microbial biomass and diversity as previoulsy observed at the landscape scale (Constancias, Saby, et al., ; Constancias, Terrat, et al., .…”
Section: Discussionmentioning
confidence: 83%
“…Besides, the landscape is a relevant scale for cropland management by farmers and for the implementation of agricultural strategies by decision‐makers. Some studies dealt with the agricultural landscape scale but evaluated basic land management categories such as forests versus grasslands versus croplands (e.g., Constancias, Saby, et al., ; Constancias, Terrat, et al., ). We now need to quantitatively integrate the range of farm systems variation and identify those farming practices which have the most impact.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation